Thickness tunable transport in alloyed WSSe field effect transistors - Karande, Shruti D.; Kaushik, Naveen; Narang, Deepa S.; Late, Dattatray; Lodha, Saurabh (Applied Physics Letters, 2016)
We report the field effect transistor characteristics of exfoliated transition metal dichalcogenide alloy tungsten sulphoselenide. WSSe is a layered material of strongly bonded S-W-Se atoms having weak interlayer van der Waals forces with a significant potential for spintronic and valleytronic applications due to its polar nature. The X-ray photoelectron spectroscopy measurements on crystals grown by the chemical vapor transport method indicate a stoichiometry of the form WSSe. We report flake thickness tunable transport mechanism with n-type behavior in thin flakes (<= 11 nm) and ambipolarity in thicker flakes. The devices with flake thicknesses of 2.4 nm-54.8nm exhibit a maximum electron mobility of similar to 50 cm(2)/V s along with an I-ON/I-OFF ratio > 10(6). The electron Schottky barrier height values of 35 meV and 52meV extracted from low temperature I-V measurements for 3.9 nm and 25.5 nm thick flakes, respectively, indicate that an increase in hole current with thickness is likely due to lowering of the bandgap through an increase in energy of the valence band maximum. Published by AIP Publishing.